Especies de Viola (Violaceae) adventicias en Argentina - Sanso, Andrea Mariel (2005)
Materials from Argentina of adventitious species of Viola were examined and four species were confirmed: V. arvensis, V. metajaponica, V. odorata and V. tricolor. V. metajaponica is lectotypified, and the identity of V. japonica is discussed. A key to identify the species, their descriptions, illustrations, ecology and geographic distribution are given.